Verification of the method to determine the moisture content in meat products - Gil, Amanda; Gavira, Adela; Camacho, Juan José; Rexach, Jesús (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2018)
Motivation There are various reason why food industries can determine humidity, becoming highly important the issue of growing microorganisms caused by an excess on water in raw materials. The normative ISO 9001:2015 is essential for the implantation of an improved orientated system having guarantees to comply with the requirements of the product or service as well as meeting customer´s expectations. Methods The drying methods are the most common ones to asses food moisture content. Although these methods give good results, it is difficult sometimes to remove all the humidity by drying. It is also important to mention that food can decompose at certain temperature so other substances can volatilize apart from water. Thus, the measurement of weight loss of the sample caused by water evaporation is made with a forced air circulation heater at atmospheric pressure, according to ISO 1442:1997. Results During the evaluation the checking of the procedures requires the application of uniform and consistent technical criteria.Due to the importance of meat and meat products because of its high protein in the human diet and its huge quantify demand that is analyzed in laboratories, it is observed by graphical representation the tendency of the obtained data. The proper temperature is 105ºC. Conclusions The method to quantify the moisture content of various meat products is valid obtaining reliable results with the possibility of its future accreditation.